Bahasa Inggris - Kurniasih, Retno; Adawiyah, Wiwiek Rabiatul; Sudjadi, Achmad (Faculty of Economics and Business, Jenderal Soedirman University, 2024)
This study aims to identify factors that influence entrepreneurial intention among Generation Z, often referred to as